Bipartite Toughness and k-Factors in Bipartite Graphs. (20th October 2008) - Liu, Guizhen; Qian, Jianbo; Sun, Jonathan Z.; Xu, Rui
Abstract : We define a new invariantt B ( G ) in bipartite graphs that is analogous to the toughnesst ( G ) and we give sufficient conditions in term oft B ( G ) for the existence ofk -factors in bipartite graphs. We also show that these results are sharp.